(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
The Vrana which are produced by different types of poisoning substances such as Sthavara visha, Jangama visha and Kritima visha are known as Vishaja vrana. Three great treatise (Brihatrayi) viz; Charaka samhita, Sushruta Samhita, and Astanga hridaya have elaborative descriptions regarding Vrana. Maharshi Sushruta has described various types of Vrana in different Sthanas of Sushruta samhita. But Sushruta has mentioned different types of Vishaja vrana mainly in Kalpasthana of Sushruta samhita. Ayurveda described various types of treatment module for these types of Vrana. Maharshi Sushruta has mentioned treatment of these types of Vrana in Chikitsa sthana and Kalpa sthana. In Chikitsa sthana of Sushruta Samhita shashtiupakrama has been mentioned for different types of Vrana treatment. A very limited literary research work has been done on the Vranokta Chikitsa of Vishaja vrana. Therefore a review study has been carried out on the Vranokta Chikitsa of Vishaja vrana mentioned in Sushruta Samhita Kalpasthana. The main aim of this study is to collect all the references of the Vranokta Chikitsa of Vishaja vrana described in Kalpasthana of Sushruta samhita. The treatment module as mentioned in Sushruta samhita under the heading of Shashti upakrama were critically analyzed with the Vranokta Chikitsa of Vishaja vrana of Kalpasthana. There is need of time to do more study and critically analysis on different treatment module of Vishaja vrana.